2021
DOI: 10.1371/journal.pone.0250987
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of cerebrospinal fluid inflammation across the spectrum of untreated HIV-1 infection, central nervous system injury and viral suppression

Abstract: Objective To characterize the evolution of central nervous system (CNS) inflammation in HIV-1 infection applying a panel of cerebrospinal fluid (CSF) inflammatory biomarkers to grouped subjects representing a broad spectrum of systemic HIV-1 immune suppression, CNS injury and viral control. Methods This is a cross-sectional analysis of archived CSF and blood samples, assessing concentrations of 10 functionally diverse soluble inflammatory biomarkers by immunoassays in 143 HIV-1-infected subjects divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 92 publications
10
51
0
Order By: Relevance
“…Altogether, these findings indicate that the CNS immune response may be an important driver of CNS pathogenesis, similar to other CNS inflammatory conditions or infections. 11 , 13 , 29 , 38 The principal difference between patient groups appeared to be in the magnitude of the immune response, suggesting that neuropathogenesis in COVID-19 with neurologic symptoms represents a continuum of inflammation, where the intensity of the inflammatory response (likely in combination with individual premorbid vulnerability) may be a determining factor in the development of CNS symptoms. In turn, CNS symptoms may reflect harmful effects on the brain measurable as neuroaxonal injury (CSF NfL).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these findings indicate that the CNS immune response may be an important driver of CNS pathogenesis, similar to other CNS inflammatory conditions or infections. 11 , 13 , 29 , 38 The principal difference between patient groups appeared to be in the magnitude of the immune response, suggesting that neuropathogenesis in COVID-19 with neurologic symptoms represents a continuum of inflammation, where the intensity of the inflammatory response (likely in combination with individual premorbid vulnerability) may be a determining factor in the development of CNS symptoms. In turn, CNS symptoms may reflect harmful effects on the brain measurable as neuroaxonal injury (CSF NfL).…”
Section: Discussionmentioning
confidence: 99%
“…Among the viruses considered in this collection, HIV likely has the most complex and intimate interactions with the immune system and inflammatory responses, both outside (i.e., systemically) and within the CNS. In both systemic and CNS compartments these interactions change over the long course of chronic infection ( 36 , 37 ). Figure 1 diagrams these interactions, dividing the systemic (left) from CNS (right) processes.…”
Section: Clinical Backgroundmentioning
confidence: 99%
“…Studies on chemokine receptor type 2 on monocyte subsets of CD14 and CD 16 suggested those as prognostic peripheral blood biomarkers of HIV‐associated neurocognitive disorders 23 and neuronal damage, 24 while higher number of activated CD8+T lymphocytes and natural killer cells were associated with lower risk of depression 25 . In a recent study of several biomarkers, blood sCD14 and neopterin correlated strongly with CSF NfL and may be helpful in predicting CNS injury 26 . Blood C‐reactive protein (CRP) has also been reported as marker for risk of cognitive impairment.…”
Section: Resultsmentioning
confidence: 99%
“…25 In a recent study of several biomarkers, blood sCD14 and neopterin correlated strongly with CSF NfL and may be helpful in predicting CNS injury. 26 Blood C-reactive protein (CRP) has also been reported as marker for risk of cognitive impairment. In one study, variability in C-reactive protein was associated with cognitive impairment in women living with HIV.…”
Section: Monocyte Activation and Other Markers Of Inflammationmentioning
confidence: 99%